STUDENT CONTRIBUTIONS IN WAQF ARE REVIEWED THROUGH FACTORS OF RELIGIOSITY, KNOWLEDGE, AND FINANCIAL ATTITUDES - Abdul Latif; Meichio Lesmana; Rusyda Afifah Ahmad; Antoni Julian (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
Waqf is one of the important instruments and has enormous potential from a social and financial perspective. There are many types of waqf, one of which is money waqf or cash waqf. Cash waqf has different characteristics from zakat and alms. Waqf has very significant benefits if the waqf is given in a productive form. However, currently, the great potential of waqf has not been implemented properly. The purpose of this study is to analyze the students' intentions in waqf which are influenced by factors of religiosity, knowledge, and financial attitudes. This research uses Structural Equation Modeling method with the Lisrel tool. The results showed that the factors of religiosity and knowledge were less influential than the factors of financial attitudes which had a stronger influence. In a sense, students' interest in spending their money in the form of alms can be seen in their financial attitude.